Теоретико-категорная характеризация развертки временных сетей Петри - Дубцов, Р.С. (Інститут програмних систем НАН України, 2004)
The intention of the paper is to study a category-theoretic characterization of a semantic representation of the behaviour of time Petri nets, which are a time extension of heavily used model for concurrency – Petri nets. First, we introduce a notion of unfolding of a time Petri net and then provide its category-theoretic characterization.